Pengaruh Pengungkapan Corporate Social Responsibility Dan Biaya CSR Terhadap Kinerja Perusahaan Pada Masa Pandemi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2019-2021 - Tri Cahyani Nabila; Dewi Sutjahyani (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure and CSR costs on company performance during the pandemic in food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange with the 2019-2021 research period. The sample in this research is 7 companies taken using purposive sampling technique. The independent variable used in this study is the disclosure of Corporate Social Responsibility (CSR) measured by 91 items according to GRI-G4 and CSR costs are measured by employee welfare costs and community costs, while the dependent variable is company performance measured using ROA, ROE and ROS. The research model used as a test tool is Partial Least Square (PLS) version 3.0. The results of the study show that Disclosure of Corporate Social Responsibility has a significant effect with the negative direction on company performance and CSR costs have no significant effect with the negative direction on company performance.